Economic choices in a warming world - Perthuis, Christian de (Cambridge : Cambridge University Press, 2011)
Since the publication of the Stern Review, economists have started to ask more normative questions about climate change. Should we act now or tomorrow? What is the best theoretical carbon price to reach long-term abatement targets? How do we discount the long-term costs and benefits of climate change? This provocative book argues that these are the wrong sorts of questions to ask because they don't take into account the policies that have already been implemented. Instead, it urges us to concentrate on existing policies and tools by showing how the development of carbon markets could dramatically reduce world greenhouse gas (GHG) emissions, triggering policies to build a new low-carbon energy system while restructuring the way agriculture interacts with forests. This provides an innovative perspective on how a post-Kyoto international climate regime could emerge from agreements between the main GHG emitters capping their emissions and building an international carbon market.
Machine generated contents note: Introduction: the opera house of Manaus; 1. Climate risk; 2. Some like it hot (climate change adaptation); 3. Building a low-carbon energy future; 4. Pricing carbon: the economics of cap-and-trade; 5. Agricultural intensification to preserve forests; 6. Pricing carbon: the economics of offsets; 7. Macroeconomic impacts: distributing the carbon rent; 8. International climate change negotiations; 9. Conclusion: risk of taking action, risk of inaction; Bibliography: thirty references; Thirty key facts; Greenhouse gas emissions in the world; Glossary of key terms.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Global warming -- Economic aspects; Climatic changes -- Economic aspects; Environmental policy -- Economic aspects; Greenhouse gas mitigation